2015
DOI: 10.1159/000371891
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic Realization of Focus in Bilingual Production of Southern Min and Mandarin

Abstract: Previously post-focus compression (PFC) - the lowering of fundamental frequency (F0) and intensity of post-focal words to below those of the same words in identical sentences with neutral focus - was found in Beijing Mandarin but not in Taiwan Southern Min and Taiwan Mandarin. This study investigated whether the presence of PFC would vary with age and language use of societal bilinguals of Southern Min and Mandarin. Three groups of bilingual speakers of Quanzhou Southern Min and Mandarin, age around 20, 40 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Secondly, our results are consistent with the previous results from Min-Mandarin bilinguals [12] in that sequential bilinguals successfully acquire the use of prosodic cues for encoding focus. The native-like production of prosodic focus marking in the younger group of Min-Mandarin bilinguals Mandarin was suggested as results of more Beijing-like inputs and intensive training of Standard Mandarin.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Secondly, our results are consistent with the previous results from Min-Mandarin bilinguals [12] in that sequential bilinguals successfully acquire the use of prosodic cues for encoding focus. The native-like production of prosodic focus marking in the younger group of Min-Mandarin bilinguals Mandarin was suggested as results of more Beijing-like inputs and intensive training of Standard Mandarin.…”
Section: Discussionsupporting
confidence: 91%
“…late bilinguals) and bilinguals who acquire two languages in early childhood (sequential bilinguals) has received considerable attention ( [9,10,11,12]). It has been found that the similarity between the learners' L1 and L2 did not necessarily lead to the attainment of native-like prosodic focus marking in late bilinguals in L2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous studies have reported differences between the production of focus prosody by native English and L2 English Mandarin speakers (Chen et al 2014, Chen 2015, Kao et al 2016, Wu & Chung 2011. For example, in a study of Mandarin and English speakers' production of corrective focus in English by Kao et al (2016), both English speakers and Mandarin speakers exhibited in-focus expansion and post-focus compression, although the Mandarin speakers differed from the English speakers in the alignment of their F0 peak and the magnitude of their intensity drop, showing a later F0 peak than that of native English speakers and a smaller intensity drop between the stressed syllable of the focused word and the following syllable.…”
mentioning
confidence: 93%